2017
DOI: 10.1186/s12870-017-1067-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs controlling grain protein concentration using a high-density SNP and SSR linkage map in barley (Hordeum vulgare L.)

Abstract: BackgroundGrain protein concentration (GPC) is a major determinant of quality in barley (Hordeum vulgare L.). Breeding barley cultivars with high GPC has practical value for feed and food properties. The aim of the present study was to identify quantitative trait loci (QTLs) for GPC that could be detected under multiple environments.ResultsA population of 190 recombinant inbred lines (RILs) deriving from a cross between Chinese landrace ZGMLEL with high GPC (> 20%) and Australian cultivar Schooner was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
11
0
1
Order By: Relevance
“…Neighbouring QTL that are linked in coupling phase are commonly observed in primary QTL analysis (Fan et al 2017; Wu et al 2015). To date, many studies have tried to dissect QTL in coupling phase using NILs or residual heterozygous lines and found that coupling QTL were partially attributed to tightly linked independent QTL (Chemayek et al 2017; Shen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Neighbouring QTL that are linked in coupling phase are commonly observed in primary QTL analysis (Fan et al 2017; Wu et al 2015). To date, many studies have tried to dissect QTL in coupling phase using NILs or residual heterozygous lines and found that coupling QTL were partially attributed to tightly linked independent QTL (Chemayek et al 2017; Shen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the case even though down‐regulation of GS1 expression under CO 2 enrichment has been reported for different TaGS1 isogenes in wheat (Buchner et al ., ; Vicente et al ., , ), possibly reflecting a decrease in NH 4 + (El Omari et al ., ; Funayama et al ., ; Goodall et al ., ; Guan et al ., ; Konishi et al ., ). The results for the cisgenic lines corroborate the importance of GS1 in maintaining grain protein concentration, as has also been highlighted through identification of QTLs in barley (Fan et al ., ) and via a positive correlation between GS activity and grain protein content in wheat cultivars (Nigro et al ., ; Zhang et al ., ). Considering the fact that extra N supply cannot offset the decline in grain protein concentration of wheat plants growing in an elevated CO 2 environment (Tausz et al ., ; Walker et al ., ), overexpression of HvGS1‐1 may thus provide a means to prevent declining grain protein concentration under elevated atmospheric CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The quality of genetic maps, however, can significantly affect the accuracy of gene mapping. This increases the density of markers distributed around the entire genome, which can improve the resolution of genetic maps [ 31 33 ]. SSR, one of the traditional gene mapping methods, was used in hulless barley, but the number of SSR markers is limited.…”
Section: Discussionmentioning
confidence: 99%